Phosphorus Pentasulfide Mediated Conversion of Primary Carbamates into Thiols - Maurya, Chandra Kant; Gupta, Pradeep Kumar (Synlett, 2017)
In this paper, we report a method for the conversion of primary carbamates into thiols in the presence of phosphorus pentasulfide (P2S5) in refluxing toluene. Presently, no method exists in the literature for conversion of carbamates into thiols and, to the best of our knowledge, it is the first report for this type of conversion. This method presents an indirect route for the conversion of alcohols into thiols via their carbamate derivatives that may be useful in the total synthesis of compounds containing a thiol functionality.
Keywords: carbamate; phosphorus pentasulfide; thiocarbamate; dithiocarbamate; thiol